2022
DOI: 10.31585/jbba-6-1-(1)2023
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Comparison of Post-Quantum Algorithms in Blockchain

Abstract: Blockchain and other Distributed Ledger Technologies have triggered widespread research and interest. This is due to their ability to create redundant, transparent, and accountable connections in various application domains while utilising asymmetric cryptography, digital signature, and hash functions. However, the current blockchain system exhibits vulnerability to attacks, especially those staged and actualised using quantum computers leveraging Grover's and Shor's algorithms. There is a need to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…2022, [21] Given the vulnerabilities of blockchain systems to quantum attacks, the study explored the performance of various post-quantum signature algorithms, such as the ECDSA, Dilithium, and Falcon, in a blockchain environment. The study identified that the main weakness is related more to the large sizes of the keys than to the signatures produced by cryptographic methods.…”
Section: Approachmentioning
confidence: 99%
“…2022, [21] Given the vulnerabilities of blockchain systems to quantum attacks, the study explored the performance of various post-quantum signature algorithms, such as the ECDSA, Dilithium, and Falcon, in a blockchain environment. The study identified that the main weakness is related more to the large sizes of the keys than to the signatures produced by cryptographic methods.…”
Section: Approachmentioning
confidence: 99%